Point of View in Women Curriculum Vitae in Modern Iraqi Literature (Journal of the College of Education for Women, 2019)
Throughout what mentioned above, It is obvious that the aware narrator in these biography models was the strongest tool in presenting the content, especially the biographies under study were written by feminine hands, striving to prove her identity by all means and ways. In addition, we can suppose that the hiding of she writer behind the character is no more than a mask, by which she want to mask herself so that she can express herself frankly and freely, especially when she talks about subjects that are inconsistent with the society, customs and traditions. It is important to refer that the existence of the participant narrator in the biographies under study does not prevent the presence of another narrator such as external or aware narrator .